Aerobic physical exercise versus dual-task cognitive walking in cognitive rehabilitation of people with stroke: a randomized clinical trial - Maeneja, Reinaldo; Silva, Cláudia R.; Ferreira, Inês S.; Abreu, Ana Maria (Frontiers in Psychology, 2023)
Introduction Stroke is a neurological deficit caused by an acute focal injury to the central nervous system due to vascular injury that can result in loss of neurological function, lasting brain damage, long-term disability and, in some cases, death. The literature reports that aerobic physical exercise, as well as dual-task cognitive walking, are used for the cognitive recovery of people with stroke. We aimed to assess whether aerobic physical exercise influences post-stroke cognitive recovery, namely performance on selective and sustained attention. We tested the hypothesis that post-stroke aerobic physical exercise leads to more significant gains than post-stroke dual-task cognitive walking. Methods We used a Randomized Clinical Trial, single-blind, parallel group, to verify the existence of differences between two groups. A total of 34 patients with subacute to chronic stroke were divided into two groups to train three times a week for 12 weeks: the aerobic physical exercise (PE) group engaged in 20 min on a treadmill, 20 min on a stationary bicycle and 5 min on a desk bike pedal exerciser per session; the dual-task (DT) gait exercise group walked for 45 min while simultaneously performing cognitive tasks per session. All participants were assessed on cognitive functioning with the Mini-Mental State Examination (MMSE) and d2 Test of Attention before acute interventions and post interventions. We have also applied a Visual Analog Scale to monitor the participants’ perceived difficulty, pre-, post-acute, and post-chronic interventions. Participants also responded to a Borg Scale of perceived exertion following the acute and the final session of chronic training. Results A mixed model ANOVA revealed a significant interaction effect with a large effect size for most of the cognitive variables under study. The variables associated with the d2 Test of Attention showed significant differences between the groups, mainly from T0 to T2. Also for MMSE, an ANOVA revealed a significant interaction effect with significant improvements from T0 to T2. Our results strongly suggest that aerobic physical exercise is more beneficial than dual-task cognitive-gait exercise since in the PE group, cognitive attention scores increase, and cognitive impairment and perception of exertion decrease, compared to the DT group. Conclusion These findings support that PE provides more significant benefits for patients post-stroke when compared to DT.